Smart Water Quality Monitoring System In Progo River, Magelang Regency, Central Java - Waluyo, Waluyo; Sari, Annisa Novita; Tri Aji, Muhammad (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Traditionally, air quality detection is done manually by means of air samples obtained locally and sent for analysis to a laboratory, which takes a long time, is expensive, and requires human resources. This technique does not provide real-time data. Therefore, there is a need for innovation and new technology that makes it easier to monitor and analyze air quality data in real-time with a microcontroller approach and certain water quality sensor parameters, where the recorded data will be recorded and sent via wireless with the Internet of Things (IoT) approach. Parameter values such as temperature, humidity, water level, turbidity, and pH in general can be properly recorded by each sensor. The goal of this research is to create measuring equipment for aquatic characteristics such as pH, water turbidity, water level, ambient air temperature, and humidity using the Thingspeak website and telegram. System design, programming the ATmega2560-based Arduino Mega microcontroller and ESP8266-based NodeMCU using the Arduino IDE, and constructing and testing equipment on a prototype scale and directly in the field are the methods employed in this research. According to the results of field testing, the water temperature sensor is capable of capturing fluctuating values ranging from 32.4 to 34.1 oC. Meanwhile, the air humidity sensor measured 33.5-35.6% humidity. The ultrasonic sensor records the height of the river water level pretty well, with a value of 28-71 cm. A pH sensor measures the pH of the water and records data in the form of water voltage ranging from 3.34 to 5.38 volts. Based on IoT, the sensor recording results are subsequently sent online and received via the Telegram application.